2015
DOI: 10.1111/nep.12377
|View full text |Cite
|
Sign up to set email alerts
|

Basal glucosuria is ubiquitous in critically ill patients

Abstract: The 'renal threshold for glucose' has never been evaluated in critically ill patients. Therefore, we aimed to investigate the renal glucose threshold in this patient group using high-sensitivity urine glucose assays. In this retrospective analysis of prospectively collected data, we analysed 100 consecutive critically ill patients from a medical intensive care unit (ICU). Arterial blood glucose and spot urine glucose were simultaneously quantified daily during the first week after ICU admission. Three hundred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…Data of this study confirm that, as has already been shown in humans (Fine, ; Rave et al, ; Wolf et al, ; Brunner et al, ) and a small cohort of non‐diabetic obese cats (Hoenig, Clark, Schaeffer, & Reiche, ), glucosuria is present in euglycemic cats. With the use of a highly sensitive assay, the mean (± SD ) urinary glucose concentration was 0.46 (±0.32) mmol/L [8.25 (±5.76) mg/dl], which is very close to the 0.7 (±0.3) mmol/L [12.6 (±5.4) mg/dl] reported by Hoenig et al ().…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Data of this study confirm that, as has already been shown in humans (Fine, ; Rave et al, ; Wolf et al, ; Brunner et al, ) and a small cohort of non‐diabetic obese cats (Hoenig, Clark, Schaeffer, & Reiche, ), glucosuria is present in euglycemic cats. With the use of a highly sensitive assay, the mean (± SD ) urinary glucose concentration was 0.46 (±0.32) mmol/L [8.25 (±5.76) mg/dl], which is very close to the 0.7 (±0.3) mmol/L [12.6 (±5.4) mg/dl] reported by Hoenig et al ().…”
Section: Discussionsupporting
confidence: 90%
“…Data of this study confirm that, as has already been shown in humans (Fine, 1965;Rave et al, 2006;Wolf et al, 2009;Brunner et al, 2015) and a small cohort of non-diabetic obese cats ( Hoenig et al (2018). Accordingly, the presence of small amounts of glucose in feline urine is by no means diagnostic for diabetes mellitus or renal glucosuria.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In the normal glycemic state, the amount of glucose in urine is relatively low, as it is mainly reabsorbed by the kidneys. Nevertheless, the renal threshold for glucose may be lowered due to a critical illness in addition to diabetes …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the renal threshold for glucose may be lowered due to a critical illness in addition to diabetes. [11] Interpretation of the results may also be complicated by diseases like coeliac disease and hypolactasia. [8] During these conditions intestinal damage leads to uncontrolled intestinal permeability which in turn increases the disaccharide concentration in the blood, and eventually in the urine.…”
Section: Discussionmentioning
confidence: 99%